PENGARUH PUNISHMENT THINKING CHAIR TERHADAP PERILAKU AGRESIF ANAK USIA 5-6 TAHUN DI KELOMPOK BERMAIN FLAMBOYAN KECAMATAN SIAK HULU KABUPATEN KAMPAR - Salawati '; Jaspar Jas; Daviq Chairilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study Aims To Know How Much Influence Thinking Chair Punishment Against Aggressive Behavior In Children Aged 5-6 Years Playgroup (KB) Falamboyan Siak Hulu District of Kampar regency. This research Consists Of Two Variables: Punishment Thinking Chair and Aggressive Behavior. Proposed hypothesis in this study are the following: There Punishment Thinking Chair Against Aggressive Behavior In Children Aged 5-6 Years Playgroup (KB) Falamboyan Siak Hulu subdistrict Kampar The study involved 16 subjects, namely 5-6 years old. Methods of data collection in this study using experimental. Data analysis techniques used in this study is a partial correlation techniques using facilities assistance program SPSS 17.0 for windos.The results showed no significant positive relationship between the Thinking Chair Punishment Against Aggressive Behavior In Children Aged 5-6 Years Playgroup (KB) Falamboyan Siak Hulu District of Kampar regency. Based on the results of test results Punishment difference Thinking Chair Against Aggressive Behavior In Children Aged 5-6 Years Playgroup (KB) Falamboyan District of Kampar Regency Siak Hulu are perangaruh Punishment 80.48 Thinking Chair terdapap aggressive behavior of children.Keywords: Thinking Punishment Chair, Aggressive Behavior